Psychometric analysis of cognitive distortions scale-urdu on patients diagnosed with mental disorders - Shakil, Muneeba; Ali, Uzma; Ali, Amena Zehra; Khan , Bushra (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the reliability and concurrent validity of Cognitive Distortions Scale-Urdu based on Beck's Cognitive Model of psychopathology on patients diagnosed with mental disorders. Method: The correlational study was conducted from June 15, 2019, to January 30, 2020, in Lahore, Pakistan, and comprised psychiatric patients of either gender aged 18-65 years from six government hospitals, including Mayo Hospital, Services Hospital, Punjab Institute of Mental Health, Sir Ganga Ram Hospital, Gulab Devi Hospital and the Combined Military Hospital. The participants completed the demographic information form and the Cognitive Distortions Scale-Urdu. The latter was re-administered after a gap of two weeks to determine its internal consistency and test-retest reliability. Feinstein Paranoia, Subjective Wellbeing and Siddiqui Shah Depression Scales were administered along with the Cognitive Distortions Scale-Urdu to determine its concurrent validity. Statistical analysis was done using SPSS 24. Results: Of the 106 patients, 56(52.8%) were recruited for reliability analysis with an overall mean age of 32.31+/-10.62 years, and 50(47.2%) for concurrent validity analysis with an overall mean age of 31.30+/-10.52 years. Correlation analysis indicated good internal consistency (?=0.87), test retest reliability (r=0.86) and moderately high concurrent validity of the scale (rang: 0.44-0.89). Conclusion: The Cognitive Distortions Scale-Urdu was found to have sound psychometric properties and was suitable for researchers to obtain quantitative estimates of the frequency and intensity of cognitive distortions in clinical samples. Key Words: Cognitive distortions scale, Reliability, Validity, Clinical population, Mental disorders. Continuous...